Multi-target bioactivity of summer quinones production in the Persian Gulf burrowing black-type sea urchin - Soleimani S.; Mashjoor S.; Yousefzadi M.; Kumar M. (My University, 2025)
After harvesting the sea urchin gonads for Japanese food “uni” echinoculture systems, the remaining shells and spines are considered waste. However, the material of shells and spines is thought to be rich in natural bioactive molecules. The current study used liquid chromatography–electrospray mass spectrometry to extract summer quinones pigment present in spines and shells of the burrowing sea urchin ‘black’ type Echinometra mathaei from the natural Qeshm Island echinoculture. Then, the biochemical, antioxidant, anti-inflammatory, antidiabetic, antibacterial, and cytotoxic activities of sea urchin quinones pigment were investigated. In terms of bioactivity, both shell and spine pigments demonstrated strong radical scavenging activity (antioxidant). The shell pigment exhibited maximum albumin denaturation inhibition (IC50 = 9.62 μg/ml) (anti-inflammatory), as well as α-amylase inhibition (92.28 percent 4.77) (antidiabetic). Pigments were discovered to have a low antibacterial effect against positive gramme bacteria, as well as low cytotoxic and embryotoxic effects when compared to Artemia salina and zebrafish (Danio rerio). For identification and quantification of pigment extracts, both the photodiode array detector and LC-ESI-MS were used. Spinochrome A, B, and C, as well as echinochrome A, were identified as bioactive quinonoid pigments. This chemical defence is discussed in relation to its algal diet and environmental conditions. In conclusion, the isolated pigments obtained from the shell and spines of E. mathaei sea urchins found to have potent bio-activity and can be used for various biomedical and pharmaceutical applications. © 2022 The Author(s)